Cosmesis in patients with breast neoplasia submitted to the hypofractionated radiotherapy with of intensity-modulated beam - Miranda,Fabiana Accioli (2018)
SUMMARY OBJECTIVE: To assess the cosmetic satisfaction of patients diagnosed with breast cancer submitted to the hypofractionated radiotherapy with IMRT (hIMRT) technique and its correlation with dosimetric data of the radiotherapy planning. MATERIALS AND METHODS: The retrospective cohort study that assessed women with a diagnosis of malignant breast neoplasia submitted to the conservative treatment or radical mastectomy and treated with hIMRT. In the period between August 2007 to December 2014, in a philanthropic / private institution, 170 records were selected. The cosmetic assessment was carried out by means of the Harvard/RTOG/NSABP scale with one-year minimum range after treatment. The collected dosimetric data were: breast / chest wall volume, volume that received 95% (V95%) and 107% (V107%) of the prescribed dose. RESULTS: The volume of the treated breasts ranged from 169 to 2.103 ml (median = 702; IQR: 535 to 914 ml). Median V95% was 86.7% (54.6-96.6%; IQR: 80.0% to 90.6%); eight (5.7%) patients had V95% higher than 95%. Median V107% was 0% (0%-16.3%; IQR: 0.0% to 0.3% and 13); 9.3% patients had V107% higher than 2%. One hundred and thirty-three (78.2%) patients responded to the cosmetic assessment: 99 (74.4%) considered the cosmetic results excellent. Significant associations between cosmetic assessment and breast volume (p=0.875), V95% (p=0.294) e V107% (p=0.301) were not found. CONCLUSION: The cosmetic results showed favorable when using hIMRT, and the lack of correlation with usual the dosimetric data illustrates the capacity of hIMRT to minimize the heterogeneity of the dose in this endpoint, even in voluminous breasts.